Szabályozóalku szabadpiaci környezetben: a budapesti taxipiac - Pál Réti (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– In April 2013, the Assembly of the Budapest Municipality radically transformed the taxi market in Budapest. This case study analyses the events that led to this decision and also the measure's immediate impact. The study is part of the research project, titled "The Unexpected Consequences and Impacts of the Market Regulation", financed by the Hungarian Scientific Research Fund. The new rules were aimed to establish "law and order" in the taxi market, and basically correspond to the main trends applied worldwide - although the municipality failed to do any studies concerning the international developments in this area. It soon became obvious that the trade unions and the employees' organizations, in their negotiation with the Budapest local Government, (ongoing from 2011) got into a subordinate position, due to their weak legitimacy. The mayor could successfully divide the participating interest groups. The unrealistic new rules had to be modified as soon as two months after their introduction. Even after this modification, the new rules impose uniform tariffs in a market, which previously had been extremely segmented: different tariffs applied to cruising on the street, preordering by phone, or hiring a taxi based on long term agreement. The result of the new rules could surprise the Municipality, if players outside the regulated market increase their share significantly.
Keywords: K23; L51; L92; L98; 330; taxi market regulation; reregulation; unexpected consequences